2011
DOI: 10.1080/13501763.2011.551078
|View full text |Cite
|
Sign up to set email alerts
|

Variation in EU member states' preferences and the Commission's discretion in the Doha Round

Abstract: During the period leading up to the 2005 WTO Hong Kong ministerial meeting and the 2006 Geneva informal meeting, European Union member states became even more strongly opposed to any further concessions on agricultural issues in the Doha Trade Round. Despite this opposition, the European Commission made a further offer which included concessions on agricultural issues. Based on data collected from Agence Europe and interviews with officials from the European Commission and the Council of Ministers, this contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…They found that agent autonomy increases with heterogeneity among principals. In EU foreign policies, Council unity is a similarly central factor for explaining Commission discretion (Conceição-Heldt 2011;De Bièvre and Eckhardt 2011;Elgström and Larsén 2010;niemann and Huigens 2011). Therefore, principal-agent scholars widely share the view that conflict among (collective or multiple) principals results in increased agent leeway.…”
Section: Theoretical Puzzle: Contestation In Collective Agentsmentioning
confidence: 99%
“…They found that agent autonomy increases with heterogeneity among principals. In EU foreign policies, Council unity is a similarly central factor for explaining Commission discretion (Conceição-Heldt 2011;De Bièvre and Eckhardt 2011;Elgström and Larsén 2010;niemann and Huigens 2011). Therefore, principal-agent scholars widely share the view that conflict among (collective or multiple) principals results in increased agent leeway.…”
Section: Theoretical Puzzle: Contestation In Collective Agentsmentioning
confidence: 99%
“…Hitherto, delegation studies on EU trade politics focuses on the Commission's role in global trade negotiations (Conceição-Heldt 2010;Dür and Zimmermann 2007;Elsig and Dupont 2012), on why the involvement of the EP in EU trade policy was long opposed by member states and trade policy experts (Eeckhout 2011;Meunier 2003), and on whether the EP's power has increased with the entry into force of the Treaty of Lisbon (Richardson 2012; Van den Putte et al 2015;Woolcock 2010). Some studies focus specifically on the discretion of the Commission and show that the preference heterogeneity of the principals with two camps of equal size and a broad negotiating mandate increases the agent's discretion (Conceição-Heldt 2011;Elsig 2010). Others show how growing capabilities, preferences and entrepreneurship lead to more emancipation of the agent from principals (Niemann and Huigens 2011).…”
mentioning
confidence: 99%
“…Some recent research shows that the delegation of authority to the Commission does not automatically maximize the EU's effectiveness in international negotiations (Carbone 2013;Conceição-Heldt 2013). A low degree of cohesiveness among member states does increase the discretion of the Commission in multilateral trade negotiations (Conceição-Heldt 2011, but this has the negative effect that other trading partners bypass and undermine the Commission's authority by negotiating informally with single member states (Conceição 2010). Cohesiveness can also lead to third party resistance and reduce effectiveness (Carbone 2013;Niemann and Bretherton 2013).…”
Section: Configuration 3: Internal Cohesiveness Has a Negative Impactmentioning
confidence: 99%